2009
DOI: 10.1186/1744-859x-8-24
|View full text |Cite
|
Sign up to set email alerts
|

The abilities of improved schizophrenia patients to work and live independently in the community: a 10-year long-term outcome study from Mumbai, India

Abstract: Background: The outcome of first episode schizophrenia has several determinants. Socioecological factors, particularly living conditions, migration, community and culture, not only affect the level of risk but also the outcome. Mega cities around the world show a unique socioecological condition that has several challenges for mental health. The present study reports on the long-term status of patients with schizophrenia in such a mega city: Mumbai, India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…In a study, individual placement and support was found to have good potential to address the outcome of first episode schizophrenia. 16 Even though many studies on first episode schizophrenia indicated the prevalence of substance abuse more in multi-episode schizophrenics, in our sample no difference was observed between the two groups for alcohol use and drug abuse. The two groups were compared for alcohol use using AUDIT (alcohol use disorders identification test) by WHO, and it was observed that alcohol use in general, was uncommon in these population.…”
Section: Discussionmentioning
confidence: 40%
See 1 more Smart Citation
“…In a study, individual placement and support was found to have good potential to address the outcome of first episode schizophrenia. 16 Even though many studies on first episode schizophrenia indicated the prevalence of substance abuse more in multi-episode schizophrenics, in our sample no difference was observed between the two groups for alcohol use and drug abuse. The two groups were compared for alcohol use using AUDIT (alcohol use disorders identification test) by WHO, and it was observed that alcohol use in general, was uncommon in these population.…”
Section: Discussionmentioning
confidence: 40%
“…This has economical, social and health implications. 16 A ten-year study on outcome of employment in schizophrenics concluded that 40% of patients could obtain employment, which prevented deterioration of health in these patients, while unemployment was a risk factor for more relapses. 17 This study focuses on symptom complex in first episode schizophrenics which can help in identifying severity of illness and effective treatment.…”
mentioning
confidence: 99%
“…Due to the different definitions and ideas used in research and the new line of thought in mental health care, there remains confusion about the concept of personal recovery among clients, their families, clinicians, policy makers and researchers ( 12 ). Furthermore, it remains unclear how different factors influence both short- and long-term personal recovery in schizophrenia and other psychotic disorders after treatment ( 13 ). There is, however, some consensus on what elements the concept of personal recovery consists of.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, as it was indicated in the present study, the number of working people is still relatively lower than the number of patients who might be capable of working during remission of schizophrenia. In spite of the fact that there are few research papers about the rate of people who could work in the remission phase, studies carried out both by Srivastava et al (9) and Zaprutko et al (2) confirm the tendency of the studentsí opinions and surmise that more than 50% of patients might be capable of working during remission of schizophrenia.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, supported employment (SE) performs a therapeutic function (3,5) and may lead to the competitive work attainment (5). Apart from that, work is associated with a significantly better quality of life for mentally ill people and contributes to ìcomplianceî and to lower rehospitalization rates, likewise (2,9,10). Thus, the improvement of the patientís situation on the labor market should in the long run bring significant savings both in terms of direct and indirect costs (4,11,12).…”
mentioning
confidence: 99%